Simplify (5+√2)(5-√2)
Answers
Answered by
5
Answer:
(√5-√2)(√5+√2) = 3
Explanation:
Simplification of
(√5-√2)(√5+√2)
= (√5)²-(√2)²
By \: algebraic\: identity \:
\boxed {(a-b)(a+b)=a^{2}-b^{2}}
= 5 - 2
= 3
Therefore,
(√5-√2) (√5+√2) = 3
••••
Hope it helps.....Pls mark as brainiest.........
Answered by
20
Answer:
hiiii mate,
......
I think this helps you......
.....
please mark me
as braienliest.....
....
Attachments:
![](https://hi-static.z-dn.net/files/dbf/bb8b106be235af80c1bf2c184353c52a.jpg)
Similar questions
Math,
6 months ago
Math,
6 months ago
Social Sciences,
6 months ago
Social Sciences,
1 year ago
Science,
1 year ago
Math,
1 year ago
Geography,
1 year ago